Javanese Islamic Tradition of Death - Mufidah, Muna (Mahesa Research Center (PT. Mahesa Global Publishing), 2022)
Customs can reflect the soul of a society or nation and are a personality of a society or nation. The level of civilization, a person's modern way of life cannot eliminate the behavior or customs that live and are rooted in society. The death ceremony is a ritual that has been carried out for generations by the community, one of which is on the island of Java as a form of respect for the spirits, as well as a form of help from living families so that the spirits are calm and acceptable to God Almighty. Belief in spirits that are still around the house and will come to the house on certain months and days gives birth to various ceremonies. This tradition is carried out every time someone dies and is carried out by the bereaved family. The death ceremony that can survive in the midst of Javanese society cannot be separated from the factor of religious understanding adopted by most Javanese people, namely the understanding of the elderly. The belief that the prayers and rewards offered by the living to the dead will reach the deceased, makes the tradition of funeral ceremonies persist, although with various differences.